The selfish crocodile book of colours - CHARLES, FAUSTIN; Terry, Michael, illustrator; Bloomsbury Publishing (Bloomsbury Publishing: London, UK, 2012)
What better way to learn colours than on a fun animal safari? From white-and-black zebras to grey elephants and green crocodiles, this book is packed with a whole host of animal friends. Learning has never been so much fun!
Colours introduced through animals and objects featuring the Selfish Crocodile and friends.
A bright and bold board book that helps young children learn colours with the Selfish Crocodile and his friends. Simple words and fun illustrations make it perfect for early learners.
Baby - 5 years
Text in English.
Keywords: Board books, Children's nonfiction,Children's picture books. Pictorial works, Juvenile literature, Early Learning